1980
DOI: 10.1056/nejm198001033020101
|View full text |Cite
|
Sign up to set email alerts
|

Molsidomine in the Treatment of Patients with Angina Pectoris

Abstract: Molsidomine, a new long-acting vasodilator, was administered intravenously (0.03 mg per kilogram of body weight) to two groups of six patients with stable anginapectoris. In the first group, studied during exercise-induced angina, the drug shortened the duration of pain and reduced electrocardiographically measured ST-segment depression, mean systemic arterial pressure, and mean pulmonary wedge pressure. Cardiac output and heart rate remained unchanged. In the second group, studied during pacing-induced angina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

1981
1981
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 25 publications
4
36
0
2
Order By: Relevance
“…27,28 In additional experiments with the selective ET B agonist IRL 1620, we demonstrated that the ET B receptor might provide evidence for ET-induced positive inotropy. 19 The present study examined whether the NO donor molsidomine, used clinically as a coronary dilating drug, 20 might unmask the positive inotropy of ET-1 by attenuating ETinduced myocardial ischemia without affecting the hemodynamics as adenosine does. Furthermore, we tested how effectively selective blockade of ET A receptors by BQ 610 21 is able to prevent ET-induced myocardial ischemia with subsequent depression of ventricular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 In additional experiments with the selective ET B agonist IRL 1620, we demonstrated that the ET B receptor might provide evidence for ET-induced positive inotropy. 19 The present study examined whether the NO donor molsidomine, used clinically as a coronary dilating drug, 20 might unmask the positive inotropy of ET-1 by attenuating ETinduced myocardial ischemia without affecting the hemodynamics as adenosine does. Furthermore, we tested how effectively selective blockade of ET A receptors by BQ 610 21 is able to prevent ET-induced myocardial ischemia with subsequent depression of ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of ET-1 was studied after pretreatment with the nitric oxide (NO) donor molsidomine, which is used clinically for treatment of myocardial ischemia. 20 The second part of the study examined the effect of ET-1 after selective blockade of the ET A receptors by the ET A receptor antagonist BQ 610. 21 Additionally, the effect of ET-1 on coronary flow and on myocardial energy metabolism under different conditions was investigated by colored microsphere technique and by determination of the myocardial high-energy phosphates.…”
mentioning
confidence: 99%
“…To treat reeunent spontaneous angina, we administered several drugs, mainly oral Ca antagonist (diltiazem [Kawai et al, 1981;Kimura and Kishida' 1981;Nakamura and Koiwaya, 1979;Rosenthal et al, 1980;Yasue et al, 1978Yasue et al, , 1979a or nifedipine [Autman et aI., 1980;Endo et al, 1976;Kawai et al, 1981;Kimura and Kishida 1981;Muller and Gunther 1977]) and/or nitrates (isosorbide dinitrate [ISDN) or molsidomine [Majid et al, 1980;Takeshita et al, 1977)). Propranolol was given to one patient (patient 15).…”
Section: Methodsmentioning
confidence: 99%
“…2). The final prescrip- tion was 16 mg of molisidomine (Majid et al, 1980) and 80 mg of nifedipine per day, and the patient experienced no form of chest pain for 22 months under medication.…”
Section: Patientmentioning
confidence: 99%